2002
DOI: 10.1128/jb.184.17.4811-4818.2002
|View full text |Cite
|
Sign up to set email alerts
|

Identification by Heterologous Expression and Gene Disruption of VisA as l -Lysine 2-Aminotransferase Essential for Virginiamycin S Biosynthesis in Streptomyces virginiae

Abstract: The visA gene of Streptomyces virginiae has been thought to be a part of the virginiamycin S (VS) biosynthetic gene cluster based on its location in the middle of genes that encode enzymes highly similar to those participating in the biosynthesis of streptogramin-type antibiotics. Heterologous expression of the visA gene was achieved in Escherichia coli by an N-terminal fusion with thioredoxin (TrxA), and the intact recombinant VisA protein (rVisA) was purified after cleavage with enterokinase to remove the Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 21 publications
0
17
0
1
Order By: Relevance
“…The streptogramin 3-HPA is derived from lysine (14,36,37), but the labeling experiment indicated that both pyridyl moieties of pyridomycin originate from L-aspartic acid, glycerol, and/or pyruvate, but lysine is not incorporated (11). Pyridyl ring formation from aspartate is known from the primary metabolism NAD biosynthetic pathway (39) (path a in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The streptogramin 3-HPA is derived from lysine (14,36,37), but the labeling experiment indicated that both pyridyl moieties of pyridomycin originate from L-aspartic acid, glycerol, and/or pyruvate, but lysine is not incorporated (11). Pyridyl ring formation from aspartate is known from the primary metabolism NAD biosynthetic pathway (39) (path a in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Biosynthesis of the Pyridyl Moieties-PyrB is an L-lysine 2-aminotransferase similar to VisA (61% identity and 70% similarity) involved in 3-HPA formation for virginiamycin biosyn-thesis in Streptomyces virginiae (14,36) and to NikC (56% identity and 69% similarity) that catalyzes the initial reaction for converting lysine to the pyridyl residue in nikkomycin D in Streptomyces tendae (37). However, L-aspartic acid instead of L-lysine (along with glycerol or pyruvic acid) was incorporated into the two pyridyl residues in pyridomycin.…”
Section: Cloning Sequencing and Analysis Of The Pyr Gene Cluster-mentioning
confidence: 99%
“…Precedent for an aminotransferase having such a function comes from Streptomyces virginae, which uses Lys 2-aminotransferase to synthesize a cyclohexadepsipeptide antibiotic (Namwat et al, 2002).…”
Section: Specific Physiological Function Of Ald1mentioning
confidence: 99%
“…VisA has been purified and shown to be a pyridoxal-phosphatedependent Lys 2-aminotransferase capable of generating 1-piperidine 2-carboxylate. 33 Inactivation of the visA gene in S. virginiae completely blocked biosynthesis of virginiamycin S 1 , and addition of 3-hydroxypicolinic acid but not pipecolic acid to the culture medium rescued this null phenotype, suggesting that VisA is required for formation of the former ( Figure 7). 33 Paradoxically, the intracellular levels of 1-piperidine 2-carboxylic acid in the visA null mutant were comparable to the wild-type organism.…”
Section: Structures and Biosynthesismentioning
confidence: 98%
“…Sequencing of DNA downstream from known regulatory genes of virginiamycin S biosynthesis in S. virginiae identified four genes, visA-D, predicted to be involved in amino acid biosynthesis. 33 Both visA and visC are predicted to encode enzymes that generate 1-piperidine 2-carboxylic acid. VisA has been purified and shown to be a pyridoxal-phosphatedependent Lys 2-aminotransferase capable of generating 1-piperidine 2-carboxylate.…”
Section: Structures and Biosynthesismentioning
confidence: 99%